An Analysis of Students Ability Using Simple Present Tense at Laboratorium Junior High School Jambi Academic Year 2024/2025 - Aprilia, Elsa; Ismiyati, Yanti; Suyadi, Suyadi (JELT: Journal of English Language Teaching, 2025)
This study aims to analyze students' ability to use simple present tense in descriptive text. The research method used is quantitative with a descriptive approach. The population of this study consisted of seventh grade students at Jambi Laboratory Junior High School in the 2024/2025 school year, with the sample including all seventh-grade students. The research instrument was a multiple-choice test used to assess students' understanding. The results showed that the average score obtained by students was 49.66. Of the 15 students tested, 2 students scored “good”, 8 students scored “fair”, and 5 students scored “poor”. The most common errors found were in the use of to be (is, am, are) and verbs in simple present tense. The conclusion of this study is that students' ability to understand simple present tense in descriptive text is in the moderate category. This finding highlights the need for more effective teaching strategies to improve students' understanding of English grammar, especially simple present tense.